MOTIVASI SISWA DALAM PEMBELAJARAN SENI TARI DI SMA NEGERI 2 KERINCI - Safwan, Lola Rizki; Safwan, Lola Rizki; Iriani, Zora; Astuti, Fuji (FBS Universitas Negeri Padang, 2019)
AbstractThis study aimed to describe the improvement of Students’ motivation in dance art learning in SMA Negeri 2 Kerinci at class X by using video. The type of this study was qualitative with analysis descriptive method. Instruments used in this study were the researcher and it was also helped by stationaries and digital camera. Data in this study were primary and secondary data. Techniques of data collection were done by using library research, questionaires, interview and taking documentation. Data was analyzed by counting the result of observation with precentage, it gave motivation category and analyzed qualitatively. The result of study showed that students’ motivation of class X-1 SMA Negeri 2 Kerinci was in good category.Keywords: student motivation, learning the art of dance